2022
DOI: 10.25259/ijpc_84_2021
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Prevention of Pressure Ulcers Among Caregivers of Patients Receiving Home-based Palliative Care

Abstract: Objectives: Pressure Ulcer (PUs) remains one of the most crucial aspects of any home-based palliative care setting. The objective of this need assessment study was to assess caregivers’ knowledge regarding the prevention of pressure ulcers (PUs) among home-based palliative care patients. Materials and Methods: Study design: This study was a quantitative cross-sectional survey. Setting: The study was conducted among caregivers of home-based palliative care patients residing in Olavanna Panchayath, Kozhikode. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…As life expectancy increases, methods used for cancer treatment progress and the prognosis of cancer changes, patients now live longer and require palliative care as the disease progresses and the terminal period becomes longer (Antony et al, 2018; Wang et al, 2018). Palliative care is an approach that aims to prevent suffering and improve quality of life for the patients and their families experiencing problems arising from life-threatening disease through early diagnosis and evaluation of pain and other problems and meeting their physical, psychosocial and spiritual needs (World Health Organization [WHO], 2022).…”
Section: Introductıonmentioning
confidence: 99%
See 1 more Smart Citation
“…As life expectancy increases, methods used for cancer treatment progress and the prognosis of cancer changes, patients now live longer and require palliative care as the disease progresses and the terminal period becomes longer (Antony et al, 2018; Wang et al, 2018). Palliative care is an approach that aims to prevent suffering and improve quality of life for the patients and their families experiencing problems arising from life-threatening disease through early diagnosis and evaluation of pain and other problems and meeting their physical, psychosocial and spiritual needs (World Health Organization [WHO], 2022).…”
Section: Introductıonmentioning
confidence: 99%
“…Usually caught unprepared for this task (Guclu et al, 2018; Duran et al, 2019), caregivers neglect their own health and face many problems in the emotional, physical and economic aspects of life (Gultas & Yılmaz, 2017; Antony et al, 2018; Chua et al, 2020; Ramasamy et al, 2021).…”
Section: Introductıonmentioning
confidence: 99%
“…Therefore, this knowledge is an essential requirement for caregivers 16 . A study in India found that half of the caregivers had poor knowledge of PU prevention 17 ; another study reported in Jordan showed that most caregivers had a relatively low level of knowledge about PU prevention 18 …”
Section: Introductionmentioning
confidence: 99%
“…Assessment of knowledge among the caregivers revealed that 50% of them had poor knowledge, 40% had average knowledge, 10% had good knowledge and none had very poor or very good knowledge. [ 7 ] The situational analysis revealed no written guidelines for caregivers of palliative care patients on pressure ulcer prevention in the setting. It enables them to take measures to prevent pressure ulcer development among palliative care patients, thereby improving the quality of life of patients receiving home-based palliative care.…”
Section: Introductionmentioning
confidence: 99%